Foreign exchange exposure and impact of policy switch - the case of Malaysian listed firms - Bacha, Obiyathulla Ismath; Mohamad, Azhar; Syed Mohd Zain, Sharifah Raihan; Mohd. Rasid @ Abdul Rashid, Mohd Eskandar Shah (Routledge Taylor & Francis, 2013)
This article undertakes an in-depth study of the foreign exchange exposure of Malaysian listed firms. We examine several issues related to firm-specific and overall exposure, including an evaluation of the efficacy of adopting a hard-peg on such exposure. Our sample consists of 158 listed firms and spans the 16 year period, 1990-2005. A multivariate model using four bilateral exchange rates is used to determine firm level exposure while panel data analysis using a random-effects Generalized Least Squares (GLS) model is used to determine system-wide or aggregate sample exposure. We find a total 71 of our sample firms to have significant exchange rate exposure, a rate substantially higher than that reported for most countries, especially developed ones. The US is by far the single most important source of exposure with 63 of sample firms exposed to it. The sign of the beta coefficient for three of the four currencies are negative, implying that our sample firms are largely net importers in these currencies. We find exposure to be time variant and dependent on the sector within which a firm operates. Interestingly, the panel data analysis which measures aggregate exposure, shows the US to be a significant source of exposure even with the adoption of the hard peg. The change in policy regime to a fixed peg following the crisis appears to have had no impact at either firm-level exposure or overall system-wide exposure.